Exposure of pregnant women and their children to pyrethroid insecticides in Rio de Janeiro, Brazil - Martins, Amanda Friaes; Santos, Aline Souza Espindola; Moreira, Josino Costa; Câmara, Volney de Magalhaes; Asmus, Carmen Ildes Rodrigues Froes; Rosa, Ana Cristina Simoes; Vineis, Paolo; Meyer, Armando (Frontiers in Public Health, 2023)
Background Pyrethroids are commonly used insecticides in Brazil. Gestational and early childhood exposure to pyrethroids has been linked to adverse health effects, including neurodevelopmental delays, behavioral issues, and endocrine disruption. This study evaluated the exposure of pregnant women and their children to pyrethroid insecticides in Rio de Janeiro, Brazil. Methods Creatinine-adjusted levels of the pyrethroid metabolites 3-phenoxy benzoic acid (3-PBA) and 4-fluoro-3-phenoxybenzyl acid (4-FPBA) were measured in the urine of 142 pregnant women and their children at birth and in the first, third, and 6th months of life. Results The geometric mean (GM) and 95% confidence interval (95% CI) of 3-PBA and 4-FPBA urinary concentrations in pregnant women were 0.50 (0.37–0.67) and 0.37 (0.05–2.90) ng/mg, detected in 47.2 and 10.6%, respectively. Urinary concentrations of 3-PBA in the children were 0.18 (0.15–0.23) ng/mg at birth, 0.36 (0.08–1.56) ng/mg at 1-month-old, 0.68 (0.36–1.27) ng/mg at 3-month-old, and 1.36 (0.77–2.42) ng/mg at 6-month-old, and the detection rates were respectively 10.8, 9.4, 20.9, and 20.7%. Discussion This study is one of the few that has evaluated the urinary concentrations of pyrethroids in newborns and children in their 1st year of life. The results of this study show that children's exposure to pyrethroids significantly increases after birth.